Spatial Flexibility in the Orang Lom House: An Interpretive Reconstruction of Orang Lom House in Bangka, Indonesia - Andina Syafrina; Rizka Felly; Juleta Nadea Anilaputri (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2026)
Spatial flexibility in the Lom people’s house (Memarong) is the main goal in this article. Memarong is the vernacular dwelling of the oldest indigenous community in Bangka Island, Indonesia. Historically linked to shifting cultivation and high mobility, Memarong is a stilt house of timber structure and thatched roof, organized as a single undivided interior that supports multiple temporary configurations. Using a qualitative–interpretative approach, the study combines field observation in Gebong Memarong traditional village with repeated interviews with key customary leaders, and comparative analysis of three floor plans drawn from literature and on-site documentation. The findings show that spatial flexibility in Memarong manifests in five main forms: (1) multifunctional space, (2) shifted space, (3) openness in space, (4) fixed and dynamic elements, and (5) spatial grouping. These are enabled by architectural elements such as the nine-column structural grid, bendul floor beams, movable partitions, and distributed storage (pare). The study concludes that Memarong’s flexible spatial system constitutes an adaptive strategy to changing household size and activities, offering design insights for contemporary housing facing space limitations and evolving needs.